THE IMPACT OF ALBEDO, CLOUD COVERS AND GLOBAL SOLAR RADIATION ON GLOBAL WARMING USING UYO COUNTY DATA, NIGERIA - I. E, Ekanem; A. A, Umoh; U. E, Akpan; J. G, Atat, (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2024)
Ways of countering the causes of global warming in the world involved all researchers. The impact of albedo, cloud covers and global solar radiation on global warming have been studied using atmospheric data from Uyo. The data was obtained from NIMET. The outcomes were achieved using Microsoft Excel and SPSS packages. The result obtained showed that albedo varies directly with cloud covers and indirectly with the surface temperature and global solar radiation. The mean values of albedo, cloud cover and global solar radiation are 0.5823 (about 58), 72.25 and 15.22358 MJmday. The challenge of low performance of the solar energy systems from April to October is possible. Uyo may be seen as an unvegetated land, devoid of snow according to this research outcome. Making Uyo a fully forested land, global solar radiation would increase, leading to a decrease in cloud cover. This practice would add to the possible way of resolving the challenge of global warming.